GRITOS ANTIIMPERIALISTAS EN LES FANTOCHES DE JACQUES ROUMAIN. - Maldonado-Cabello, Verónica (Revista Chilena de Literatura, 2024)
This article proposes a reading of the novel Les Fantoches by Jacques Roumain, whose historical-social setting focuses on the military occupation of the United States in Haiti (1915-1934) and on a bourgeois society that is assimilated with European / French culture and has become an accomplice of the invading country. From the approaches of the Haitian indigenous movement of anti-imperialist resistance and in articulation with the text "El Grito" by Gabriela Mistral, this article focuses on the representations of the young bourgeois society and its appearances, of the role of the writer in the context of the American occupation, and of the elements of popular culture that are briefly presented in the novel. The analysis seeks to show the implications that cultural mimicry, complicity with the occupation and the interference of Haitian folklore, have for bourgeois society through its characters.